Individual Substitution Mutations in the AID C Terminus That Ablate IgH Class Switch Recombination - Kadungure, Tatenda (PLoS One, 2015)
Activation-induced cytidine deaminase (AID) is essential for class switch recombination (CSR) and somatic hypermutation (SHM) of Ig genes. The C terminus of AID is required for CSR but not for SHM, but the reason for this is not entirely clear. By retroviral transduction of mutant AID proteins into aid (-/-) mouse splenic B cells, we show that 4 amino acids within the C terminus of mouse AID, when individually mutated to specific amino acids (R190K, A192K, L196S, F198S), reduce CSR about as much or more than deletion of the entire C terminal 10 amino acids. Similar to ΔAID, the substitutions reduce binding of UNG to Ig Sμ regions and some reduce binding of Msh2, both of which are important for introducing S region DNA breaks. Junctions between the IgH donor switch (S)μ and acceptor Sα regions from cells expressing ΔAID or the L196S mutant show increased microhomology compared to junctions in cells expressing wild-type AID, consistent with problems during CSR and the use of alternative end-joining, rather than non-homologous end-joining (NHEJ). Unlike deletion of the AID C terminus, 3 of the substitution mutants reduce DNA double-strand breaks (DSBs) detected within the Sμ region in splenic B cells undergoing CSR. Cells expressing these 3 substitution mutants also have greatly reduced mutations within unrearranged Sμ regions, and they decrease with time after activation. These results might be explained by increased error-free repair, but as the C terminus has been shown to be important for recruitment of NHEJ proteins, this appears unlikely. We hypothesize that Sμ DNA breaks in cells expressing these C terminus substitution mutants are poorly repaired, resulting in destruction of Sμ segments that are deaminated by these mutants. This could explain why these mutants cannot undergo CSR.